INVESTIGATING THE INFLUENCE OF LIFESTYLE, SOCIAL INFLUENCE, AND ATTITUDE ON INTENTION TO USE E-WALLETS - Shelvy Kurniawan; Daffa Zaqi Pramanaputra (Suluh Adiluhung Publisher (SAPub), 2026)
Technology has made a huge change for everyone in their daily life. With the existence of digital technology like this, it has provided a lot of convenience for everyone. Like the activities of each person in making their transactions. In the era of digital technology like today, everyone has changed the way they make payments to new technologies such as implementing the use of electronic wallet services. This study aims to determine the influence of lifestyle and social influence on e-wallet usage intention with attitude as its mediation. This study uses a quantitative method using a questionnaire that is distributed and uses 96 people as respondents. The respondents given are intended for everyone who uses electronic wallet services as their payment method. The results of this study indicate that lifestyle has a positive and significant influence on e-wallet usage intention, lifestyle has a positive and significant influence on attitude, social influence has a positive and significant influence on e-wallet usage intention, social influence has a positive and significant influence on attitude, and attitude has a positive and significant influence on e-wallet usage intention.